Short-wavelength undulatory extinction in quartz recording coseismic deformation in the middle crust – an experimental study - Trepmann, C. A.; Stöckhert, B. (Solid earth (Göttingen), 2013)
Deformation experiments are carried out on natural vein quartz in a modified Griggs-type solid medium apparatus to explore the preservation potential of microfabrics created by crystal-plastic deformation at high stress, overprinted during subsequent creep at lower stress. A corresponding stress history is expected for the upper plastosphere, where fault slip during an earthquake causes quasi-instantaneous loading to high stress, followed by stress relaxation. The question is whether evidence of crystal-plastic deformation at high stress, hence an indicator of past seismic activity, can still be identified in the microstructure after overprint by creep at lower stresses. First, quartz samples are deformed at a temperature of 400 °C and constant strain rate of 10−4 s−1 ("kick"), and then held at 900 to 1000 °C at residual stress ("creep"). In quartz exclusively subject to high-stress deformation, lamellar domains of slightly differing crystallographic orientation (misorientation angle < 2°) and a few tens of micrometres wide occur. In the transmission electron microscope (TEM), these areas show a high density of tangled dislocations and cellular structures. After "kick and creep" experiments, pronounced short-wavelength undulatory extinction (SWUE) is observed in the polarization microscope. The wavelength of SWUE is up to 10 μm, with oscillatory misorientation of up to a few degrees. TEM inspection reveals domains with high density of dislocations and differing diffraction contrast bound by poorly ordered dislocation walls. Only zones with exceptional damage generated during high-stress deformation are replaced by small new grains with a diameter of about 10 to 20 μm, forming strings of recrystallized grains. For large original grains showing SWUE, the Schmid factor for basal ⟨ a ⟩ glide is found to be high. SWUE is taken to reflect high-stress crystal-plastic deformation, the modified microstructure being sufficiently stable to be recognized after subsequent creep as an indicator of past seismic activity.